A CASE STUDY ON MAP ACTIVITIES WITH CHILDREN OF KINDERGARTEN AGE - Senol, Halil Ibrahim; Gokgoz, Turkay (BULGARIAN CARTOGRAPHIC ASSOC, 2018)
For the purpose of measuring the ability of students at the kindergarten level in Turkey in terms of using maps, three activities were carried out with a total of 67 students. In the first activity, a total of 6 questions asked for the children with the aim of measuring their abilities in 1) matching the entities in the real world and their representations on the map, 2) determining topological relationships, and 3) matching a 3D (relief) representations and 2D (planimetric) representations. In the second activity, they were asked a total of 3 questions with the aim of measuring their abilities in 1) matching the objects in the classroom and the representations on the classroom plan, and 2) determining topological relationships. Finally, a treasure map activity was performed. As a result, it has been determined that there are differences between 60% and 80% in terms of abilities in these activities.
Keywords: Cartography; Map Activities; Matching; Topological Relationships; Children of Kindergarten Age; Geography